Concept study moments in mathematics teacher training - Mocrosky, Luciane Ferreira [UNESP]; de Fátima Custódio Dambros de Carlos, Vanessa; Panossian, Maria Lucia (FapUNIFESP (SciELO), 2024)
In this work, our objective is to present and discuss manifestations related to the understanding of concepts by participating teachers in the Pedagogical Workshop of Mathematics (OPM), a continuous education process that took place in São Bento do Sul (SC). The proposal is supported by the Teaching Guiding Activity as a theoretical-methodological basis grounded in the principles of historical-dialectical materialism, historical-cultural theory, and activity theory. Based on these assumptions, we understand that the teacher's activity involves the intentional and systematic organization of actions that trigger in students the processes of appropriation of concepts and human historical-cultural experiences. As we present the analysis of one of the formative moments in the OPM, we identified shortcomings in teachers' understanding, and this affects the way they organize teaching actions related to concepts. Thus, what we want to draw attention to is that the teacher needs to theoretically understand the teaching object, the concept, its historical-logical movement, the needs, and the relationships established in its constitution. Our argument is that teacher training processes should be constituted as activities, placing the teacher in a learning process, mobilizing them to the need for appropriate conceptual relationships articulated to pedagogical processes of teaching. In this sense, we emphasize the work in the OPM, which is based on the assumptions of the Teaching Guiding Activity and constitutes a possibility to organize formative spaces that contemplate actions focused on theoretical and practical articulation, collective study, and understanding of concepts in an environment of reflective learning for teachers.
Momentos de estudo do conceito nas formações de professores de matemática
Keywords: Teacher training; Teaching Guiding Activity; Understanding of concepts